Treatment for Stanford type B aortic dissection with insufficient anchoring region using castor integrated branched aortic stent graft - Chen, Weiqing; Liu, Dabing; Chen, Tao; Liu, Jian; Guo, Yi; Ye, Bo (Frontiers in Cardiovascular Medicine, 2024)
Background To investigate the clinical efficacy of Castor integrated branched aortic stent graft for the treatment of Stanford type B aortic dissection with insufficient anchoring area. Methods Retrospective analysis of clinical data of 26 patients with Stanford type B aortic dissection with insufficient anchoring region (<15 mm) treated by Castor branched aortic stent graft from September 2018 to June 2022 at Ganzhou People's Hospital, including 23 acute cases and 3 chronic cases. Results Surgical procedures were successfully performed in all 26 patients, and during the perioperative period no complications occurred, such as cerebrovascular accident, stenosis or occlusion of left subclavian artery, progression of reverse avulsion of aortic dissection, and paraplegia. During the operation 2 patients had a small amount of type I endoleak, which disappeared during the postoperative follow-up. The other patients had good postoperative follow-up results. Review of the aortic CTA indicated good stent morphology with patency of the left subclavian artery. Conclusions The Castor integrated branched aortic stent graft expanded the indications for endoluminal treatment for Stanford type B aortic dissection, which can avoid open surgery and has good clinical outcomes.